2015
DOI: 10.17116/jnevro20151155157-63
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of cerebrolysin effect on BDNF level in patients with post stroke aphasia depending on carbohydrate metabolism disorders

Abstract: The use of cerebrolysin in the complex treatment of patients with post stroke aphasia of different severity improves the prognosis of their rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In another study, cerebrolysin was confirmed to reduce neuronal cell death and increase neurogenesis and brain functions in diverse brain diseases, such as mouse closed head injury (mCHI) and stroke (Zhang L. et al, 2013;Zhang Y. et al, 2013). In addition, it has been shown in many previous studies that cerebrolysin promotes neuroprotection and neurogenesis by increasing the expression of factors such as NGF and brain-derived neurotrophic factor (BDNF) (Rockenstein et al, 2015;Shishkova et al, 2015;Alvarez et al, 2016). In this way, cerebrolysin has shown positive effects in several brain diseases.…”
Section: Introductionmentioning
confidence: 93%
“…In another study, cerebrolysin was confirmed to reduce neuronal cell death and increase neurogenesis and brain functions in diverse brain diseases, such as mouse closed head injury (mCHI) and stroke (Zhang L. et al, 2013;Zhang Y. et al, 2013). In addition, it has been shown in many previous studies that cerebrolysin promotes neuroprotection and neurogenesis by increasing the expression of factors such as NGF and brain-derived neurotrophic factor (BDNF) (Rockenstein et al, 2015;Shishkova et al, 2015;Alvarez et al, 2016). In this way, cerebrolysin has shown positive effects in several brain diseases.…”
Section: Introductionmentioning
confidence: 93%
“…In previous studies using rat ischemia models, it was found that when BDNF synthesis was blocked, the beneficial effects on the recovery of skilled reaching were mostly negated [79], while intravenous administration of BDNF significantly enhanced the functional motor recovery of the treated rats, compared to the untreated controls [80,81]. Behavioral and physical therapies, such as aerobic/physical exercise, transcranial direct current stimulation (tDCS), and extremely lowfrequency electromagnetic field therapy (ELF-EMF), were all found to increase the blood and/or brain levels of BDNF [72,77,[82][83][84][85]. In addition, BDNF-mediated learning memory may also be partially involved in the poststroke rehabilitation of motor function and language relearning [86-88].…”
Section: Bdnf Induces Neuroplasticity In Poststroke Rehabilitationmentioning
confidence: 99%
“…a.u., arbitrary units. References: TNF-α 134 ; NGF 135,136 ; VEGF 137,138 ; BDNF 139 ; IGF-1 76,[131][132][133] ; Neuroreaction (Neurogenesis, Neuroplasticity, Neuroinflammation) 138,140,141 ; Cerebrolysin effects on TNF-α, 61,142 NGF, 63 VEGF, 66 BDNF, 64,65 and IGF-1. 61 [Color figure can be viewed at wileyonlinelibrary.com] neurons.…”
Section: Neurogenesis In Tbimentioning
confidence: 99%
“…1.4 | NTFs in dementia, stroke, and TBI pathologies NTF profiles are imbalanced across various CNS pathologies, which is why pharmacological interventions with the ability to modulate NTF expression are of particular interest. One such drug is Cerebrolysin, which has been reported to influence the expression of TNF-α, 61,62 NGF, 63 IGF-1, 61 BDNF, 64,65 and VEGF. 66 Intriguingly, these five NTFs are also demonstrably imbalanced in brain pathologies such as dementia, 67-71 stroke [72][73][74][75][76] and traumatic brain injury (TBI) [77][78][79][80][81] (Supporting Information: Figure S1).…”
Section: Ntfs: Neuroinflammationmentioning
confidence: 99%
See 1 more Smart Citation